Edukasi dan Pemberian Bantuan pada Pasien Tuberkolosis - Tohirin, Tohirin Tohirin; Amaliyah, Evy Rizki; Amaliyah, Evy Rizki (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2018)
Tuberculosis (TB) is one of the deadly infectious diseases which is still a concern of the world community. According to the World Health Organization (WHO) report, in 2013, about 9 million people suffered from tuberculosis and 1.5 million died. This disease attacks various regions in Indonesia, one of them is Tangerang, Banten. Based on data from Puskesmas in Tangerang City, the number of suspect cases of pulmonary tuberculosis in 2015 were 7,455 cases, while the number of new cases of BTA (+) found as many as 1.005 people, and the number of cases of duration of pulmonary tuberculosis were 661 people. Meanwhile, according to gender, found as many as 1017 cases in men and 649 cases in women. This problem is then that pushed the Faculty of Health Sciences Muhammadiyah University Prof. DR. HAMKA reduces the students through the field propagation program. Students educate people about TB disease and raise funds to help people with TB.